ChemInform Abstract: A Mild and Simple One‐Pot Synthesis of 2‐Substituted Benzimidazole Derivatives Using DDQ as an Efficient Oxidant at Room Temperature. Issue 23 (June 2015) - Naeimi, Hossein; Babaei, Zahra
Abstract A wide range of the title compounds (III) (14 examples) are smoothly and efficiently synthesized by one‐pot reaction of o‐phenylenediamine (I) with various aromatic aldehydes under mild reaction conditions.